Studying the Documentation Process in Digital Forensic Investigation Frameworks/ Models - Abbas, Talib M. Jawad (Al-Nahrain Journal of Science, 2018)
With the proliferation of the digital crime around the world, there are numerous and diverse digital forensic investigation models for driving digital investigation processes. Now more than ever, it must be a criminal investigation to obtain digital evidence which wouldn’t be admissible in court. Therefore, digital forensic investigation should be implemented successfully, and there are a number of significant steps that should be taken into account. Each step and phase produces documents that are essential in understanding how the investigation process is built.The aim of this paper is to study models/ frameworks for the digital forensic investigation over a time period of ten years and find out the degree and level of attention to the process of documentation. This paper also includes definitions and descriptions of the basic and core concepts that the frameworks/ models use.